2021
DOI: 10.3904/kjim.2019.117
|View full text |Cite
|
Sign up to set email alerts
|

Colonoscopy quality in community hospitals and nonhospital facilities in Korea

Abstract: Background/Aims: High-quality colonoscopy is essential to reduce colorectal cancer-related deaths. Little is known about colonoscopy quality in non-academic practice settings. We aimed to evaluate the quality of colonoscopies performed in community hospitals and nonhospital facilities. Methods: Colonoscopy data were collected from patients referred to six tertiary care centers after receiving colonoscopies at community hospitals and nonhospital facilities. Based on their photographs, we measured quality indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…For instance, overall cecal intubation rate of colonoscopy and complete examination rate of capsule endoscopy were 94.4% and 93.66% respectively, while 93.1% and 83.7% in Korea. [ 43 , 44 ] The success rate of selective deep cannulation during ERCP was 95.67%, and this rate was 93.1% in Sweden in the same year. [ 20 ] Besides, based on the previous results from 5-year consecutive nationwide surveys and multicenter prospective studies, [ 45 ] the success rate of extraction of common bile duct stones ( < 1 cm) and proportion of pancreatitis after ERCP were 94.2% and < 10% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, overall cecal intubation rate of colonoscopy and complete examination rate of capsule endoscopy were 94.4% and 93.66% respectively, while 93.1% and 83.7% in Korea. [ 43 , 44 ] The success rate of selective deep cannulation during ERCP was 95.67%, and this rate was 93.1% in Sweden in the same year. [ 20 ] Besides, based on the previous results from 5-year consecutive nationwide surveys and multicenter prospective studies, [ 45 ] the success rate of extraction of common bile duct stones ( < 1 cm) and proportion of pancreatitis after ERCP were 94.2% and < 10% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the mean age of the patients who underwent colonoscopy was 43.8 years, which is comparable to other similar studies done in Nepal 5 7 . However, the median age of patients undergoing colonoscopy was reported to be 62.5 years in a study done in the USA, 57 years in a general hospital in the UK and 59 years in a study done in South Korea 10 12 . In Nepal, the use of colonoscopy as a screening tool for colorectal carcinoma (CRC) in older individuals has not been widely established yet.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to be familiar with quality indicators and continuously measure them in routine practice [ 72 , 73 ]. Studies have shown that the monitoring and reporting of colonoscopy quality indicators in Korea are suboptimal [ 74 , 75 ]. With the recent increase in CRC, the interest in and concerns about colonoscopy are also increasing.…”
Section: Discussionmentioning
confidence: 99%